Removal of endocrine disrupting compounds using a membrane bioreactor and disinfection. Issue 2 (1st March 2007) - Lemanik, S; Spring, A J; Andrews, Robert C; Yang, P; Bagley, David M
Abstract : Membrane bioreactors (MBRs) in combination with appropriate disinfection may provide sufficient wastewater treatment to produce effluent suitable for non-potable reuse. However, the ability of this technology combination to remove endocrine disrupting compounds (EDCs) has not been well studied. This study found that prior to disinfection a MBR removed greater than 96% of the influent cholesterol, coprostanol, and stigmastanol from municipal wastewaters compared to greater than 85% removal in a conventional treatment plant receiving the same influent. MBR effluent EDC concentrations were also lower for estrone, 17 α -ethynylestradiol, and bisphenol A. Disinfection of MBR effluent with chlorine, chloramines, and chlorine dioxide provided no significant additional removal of estrone, 17 β -estradiol, or 17 α -ethynylestradiol but could remove 95% of added bisphenol A. Ultraviolet light at a dose appropriate for non-potable reuse did not affect removal of the target EDCs.